How to manage blocked intramedullary canal while reaming during hip arthroplasty - Bansal, Harish; Jajoriya, Laxmi Narayan; Verma, Aditya (International Journal of Research in Orthopaedics, 2023)
Blockage of femoral canal while doing hemiarthroplasty is rare finding. Before inserting the femoral stem trial we should manage this blockage adequately to prevent iatrogenic fracture. Herein, we present a case of fracture neck of femur right in a 79-year-old male who presented with history of right hip pain and later was diagnosed with neck of femur fracture subcapital type that was treated with cementless hemiarthroplasty. In conclusion, if the canal is blocked, start with small diameter (K-wire), then insert guide wire and then reaming over it to open the blocked canal, do not hammer directly to prevent iatrogenic fracture. Go sequentially to open the blockage. First open the marrow then insert trial stem.